2023
DOI: 10.1007/s10067-023-06621-9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood rheumatic diseases: bites not only the joint, but also the heart

Abstract: Cardiovascular involvement in juvenile rheumatic diseases is the primary manifestation in paediatric vasculitis and a major organ manifestation in paediatric connective tissue diseases. Though coronary vasculitis is the prototypical manifestation of Kawasaki disease, it can also be seen in patients with polyarteritis nodosa. Pericarditis is the most common manifestation seen in juvenile rheumatic diseases like systemic onset JIA, and lupus. Cardiac tamponade, valvular insufficiency, aortic root dilatation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…Numerous long-term follow-up studies conducted both domestically and internationally have revealed that Kawasaki disease, particularly when accompanied by CAL, serves as a hazard factor for ischemic heart disease. 27 , 28 The progression of CAL in KD is attributed to the impaired function of coronary endothelial cells resulting from the interplay between inflammation and oxidative stress. 29 , 30 The current lack of specific laboratory indicators for early diagnosis of Kawasaki disease and Kawasaki disease CAL poses a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous long-term follow-up studies conducted both domestically and internationally have revealed that Kawasaki disease, particularly when accompanied by CAL, serves as a hazard factor for ischemic heart disease. 27 , 28 The progression of CAL in KD is attributed to the impaired function of coronary endothelial cells resulting from the interplay between inflammation and oxidative stress. 29 , 30 The current lack of specific laboratory indicators for early diagnosis of Kawasaki disease and Kawasaki disease CAL poses a challenge.…”
Section: Discussionmentioning
confidence: 99%